Independent Measures of Utricular Function: Ocular Vestibular Evoked Myogenic Potentials Do Not Correlate With Subjective Visual Vertical or Fundus Photographic Binocular Cyclorotation - Hösli, Sarah; Straumann, Dominik (Frontiers in Neurology, 2021)
Ocular vestibular evoked myogenic potentials (oVEMP), subjective visual vertical (SVV) and fundusphotographically measured binocular cyclorotation (BCR) are diagnostic tests to assess utricular function in patients with vertigo or dizziness. In 138 patients with chronic vertigo or dizziness we asked whether the asymmetry ratio of oVEMP (normal, right side pathological, left side pathological) could predict the SVV deviation (normal, rightward deviation, leftward deviation) or BCR (normal, cyclorotation to the right, cyclorotation to the left). There was no correlation between oVEMP and SVV and between oVEMP and BCR, while SVV and BCR correlated highly. Although both oVEMP and SVV measure aspects of utricular function, our findings demonstrate that oVEMP and SVV are not redundant and may reflect different utricular pathologies. The role of fundusphotographic BCR maybe relegated to only confirm unclear SVV results in vestibular diagnostic workup.